Dynamic Coefficients or Response Spectra of Structures to Earthquake? - Evgeny N. Kurbatsky; Vladimir L. Mondrus (Academia: Архитектура и строительство, 2019)
There are big differences in definition of the seismic input in the norms of the Russian Federation code and in the foreign countries standards. Almost all normative documents and guidelines for the earthquake resistance analysis of structures in technically developed countries of the world used the concept of the response spectra concept.